2020
DOI: 10.5194/acp-20-7955-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sea spray aerosol organic enrichment, water uptake and surface tension effects

Abstract: Abstract. The aerosol-driven radiative effects on marine low-level cloud represent a large uncertainty in climate simulations, in particular over the Southern Ocean, which is also an important region for sea spray aerosol production. Observations of sea spray aerosol organic enrichment and the resulting impact on water uptake over the remote Southern Hemisphere are scarce, and therefore the region is under-represented in existing parameterisations. The Surface Ocean Aerosol Production (SOAP) voyage was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 82 publications
3
47
0
Order By: Relevance
“…In any case, PMA CCN is found to have little seasonal variability relative to biogenic CCN (Vallina et al, 2006), likely driven by small seasonal differences in wind speed (Saliba et al, 2019). Organic enrichment of PMA in biologically productive waters may further reduce their hygroscopicity (Burrows et al, 2018;Cravigan et al, 2020;Law et al, 2017;Meskhidze and Nenes, 2010).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In any case, PMA CCN is found to have little seasonal variability relative to biogenic CCN (Vallina et al, 2006), likely driven by small seasonal differences in wind speed (Saliba et al, 2019). Organic enrichment of PMA in biologically productive waters may further reduce their hygroscopicity (Burrows et al, 2018;Cravigan et al, 2020;Law et al, 2017;Meskhidze and Nenes, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Increased CDNC is also shown to correlate with enhanced cloud fraction, significantly increasing overall cloud shortwave forcing (Rosenfeld et al, 2019). If cloud droplets precipitate, CN and CCN concentrations are reduced through precipitation scavenging (Croft et al, 2010;Stevens and Feingold, 2009). In this study, we discuss airborne aerosol measurements in the SO region south of Australia (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…shown sea spray aerosol (SSA) to be an important source for primary Arctic aerosol particles. SSA is a complex mixture of sea salt and organic matter 28,29 , and can also contain a fraction of semi-volatile organic compounds (SVOCs) 30 . SSA are produced by bubble bursting following wave breaking in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a low O : C ratio of bulk organic aerosol indicates a large fraction of aliphatic or lipid-like compounds with low solubility and hygroscopicity, whereas a high ratio corresponds to more oxidised and carbohydrate-like compounds with higher solubility and hygroscopicity, e.g. polysaccharides 29 . Molecular-level composition data can thus enable calculations of e.g.…”
Section: Introductionmentioning
confidence: 99%
“…SSA is composed of an internal mixture of inorganic salts and biogenic organic material (Cravigan et al, 2020;Ault et al, 2013). Typically it forms coarse-mode aerosol with mean diameters in the range of approximately 200-500 nm (Quinn et al, 2017;Lewis et al, 2004), although substantial number concentrations have been observed at smaller sizes, containing enhanced organic fractions (Andreae and Rosenfeld, 2008).…”
Section: Introductionmentioning
confidence: 99%